Question: simplify expresion by redefining expression in the previous solution step

Say I have ,

sol1 := C*vout*vin/(Iout*L*k^2)

and I want to simplify this expression by replacing  vin/Iout with omega0*Lm.

Then I need to simplify it further by noting that Lm= k*L, and that C = 1/(omega0*L), so that the answer is only in terms of vout, omega0 , and k.

I tried eval(sol1, vin/Iout = omega*Lm) initially to step through the first substitution, but that just returned the same expression.

Thank you.

Please Wait...